2021
DOI: 10.3390/polym13111839
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Structural Properties and Performances of Graphene Oxide Incorporated into Chitosan/Poly-Lactic Acid Composites: CS/PLA versus CS/PLA-GO

Abstract: In this work, to fabricate a novel composite consisting of chitosan/poly-lactic acid doped with graphene oxide (CS/PLA-GO), composites were prepared via solution blending method to create various compositions of CS and PLA (90/10, 70/30 and 50/50CS/PLA-GO). Graphene oxide (GO) was added into a PLA solution prior to blending it with chitosan (CS). The surface morphology and structural properties of synthesized composites were characterized using FT-IR, SEM and XRD analysis. The performances of synthesized compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In another investigation [ 173 ], solution blending was used to fabricate chitosan/PLA composites doped with graphene oxide (GO). GO was added into a PLA solution before blending it with chitosan.…”
Section: Pla’s Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another investigation [ 173 ], solution blending was used to fabricate chitosan/PLA composites doped with graphene oxide (GO). GO was added into a PLA solution before blending it with chitosan.…”
Section: Pla’s Modificationsmentioning
confidence: 99%
“…The study concluded that the prepared composites with GO have high potential to be used in biomedical applications such as drug delivery. Furthermore, the developed composites can be also utilized in food packaging applications [ 173 ].…”
Section: Pla’s Modificationsmentioning
confidence: 99%
“…The peak assignments of neat PLA are shown in Figure 6 a, and they are consistent with the values reported in the literature [ 42 ]. Infrared bands can be observed in the region between 2996 and 2946 cm −1 , and they are ascribed to the asymmetric v (CH 2 ) and symmetric v (CH 2 ), which are readily recognizable in the spectra of PLA-acetone and GO/PLA [ 43 ]. The bands at 1454 and 1382 cm −1 correspond to bending vibrations of the methyl group (-CH 3 ) in PLA [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 7 , in the case of pristine PLA, major weight loss occurred at 360 °C, indicating its decomposition with a total mass loss of 98.12%. By contrast, the TGA curve of GO/PLA revealed one weight loss event at 339 °C, and the lowered decomposition temperature was attributed to the reaction between GO and PLA [ 43 ]. Unexpectedly, the GO peak was not observed, or it could have merged with the PLA peak, although GO decomposition was expected to occur at approximately ~258 °C owing to the removal of the oxygen-containing groups of GO [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the hydrophilic nanoparticle granules and the hydrophobic PLA have a weak interfacial contact. To overcome these restrictions, researchers looked into modifying, processing, and the qualities of mixes to improve phase compatibility (Martinez Villadiego et al 2021, Mohamad et al 2021). These particles have some of the bene ts of natural polymers and some of the general properties of nanomaterials, such as tiny size, surface, and interface effects.…”
Section: Introductionmentioning
confidence: 99%